The Reaction of Poverty to Consumption and Inflation in Indonesia - Rizkina, Azka; Nurhayati, Nurhayati; Rasyidin, M; Saputra, Al Mahfud; Ariga, Hijrah Purnama Sari (SAINTIS Publishing, 2024)
This study investigates the reaction of poverty to consumption and inflation in Indonesia, utilizing the Autoregressive Distributed Lag (ARDL) method to explore the dynamic relationships between these key economic variables. The analysis is based on time-series data spanning from 2012 to 2023, comprising a total of 340 samples from 34 provinces across Indonesia. The findings reveal that both consumption and inflation exert a significant influence on poverty levels, with effects observable in both the short and long term. Specifically, consumption and inflation demonstrate a statistically significant relationship at a 5 percent significance level in the short term. However, in the long term, inflation’s effect is identified at a slightly higher significance level of 10 percent, indicating its persistent but somewhat weaker influence compared to consumption. These results highlight critical insights into the economic mechanisms that drive poverty in Indonesia, underlining the pivotal roles of consumption patterns and inflationary pressures. The research emphasizes the importance of targeted economic policies to manage these variables effectively to reduce poverty. For instance, promoting sustainable consumption and mitigating inflation’s adverse impacts can foster greater economic stability and resilience among vulnerable populations. By addressing these factors, policymakers can implement more effective strategies to achieve equitable economic growth and social welfare.